Figure X. What a singularity looks like outside cosmology: where equations stop working. - Hamidi, Nabil (My University, 2025)
Singularities are commonly treated as rare cosmological features confined to black holes and the origin of the universe. In this paper, I argue that singularities are not exceptional objects but expressions of a deeper structural condition: the collapse of governing law. A singularity is the point at which a physical description loses definability, prediction fails, and the authority of the model effectively falls to zero. While this behavior appears in general relativity as geodesic incompleteness, the same pattern is observable in ordinary systems — in biological tissues, material failure, turbulence, fracture, phase transitions, and other regions where equations cease to apply. Rather than signifying infinite energy or literal physical infinities, these divergences indicate that the current theory has reached its boundary. By treating the GR singularity as one instance of a universal phenomenon — anarchy (0) — this paper reframes singularities as everyday, observable structures. This perspective expands singularity theory beyond cosmology and reveals that the places where law ends are not remote; they surround us.